6 - Brief Assessment of Higher Education Governance in Ethiopia: Reflection on the Leap of the Decade - Melu, Anteneh (Journal of Higher Education in Africa, 2022)
The article attempts to explore the overall patterns of governance of higher education institutions in Ethiopia in the recent past that witnessed the massification of higher education institutions, and to investigate and display the change and continuity that have been observed in the governance of these institutions. It tries to offer some insight concerning the governance aspect in the ever-expanding and the most pressing issue of the Ethiopian higher education system. The paper presents a snapshot of the contemporary higher education development in the past two decades and associated features in Ethiopia by identifying the central issues related to principally governance, the legal framework and the political context. As the boom of higher education in the country became prevalent the governance bottleneck is one evident issue that vehemently impacts the missions of the institutions. The indispensable governance issues did not equally accompany the expansion of the higher education institutions in the last decade, and structure and other resultant issues that need to be adopted and made plain. In addition, the vivid demarcation between the institutions and the interested political groups at various levels, and the roles and relationships among them need close observation and appraisal so that the much-needed quality education and the contribution of research and community service will be significantly realised.